2023
DOI: 10.1177/10760296231200224
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulants for Inferior Vena Cava Agenesis

Michael Iarossi,
Cedric Hermans

Abstract: Deep vein thrombosis (DVT) is common in the general population, with an annual incidence of 1 to 2 per 1000 people. Inferior vena cava agenesis (IVCA) increased the risk of developing DVT and is found in approximately 5% of young adults (20-40-year-olds) diagnosed with unprovoked proximal DVT. IVCA can be caused by a defective embryological process, or be a result of intrauterine or perinatal thrombosis. Its estimated incidence in the general population ranges from 0.0005% to 1%, usually involving a partial ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…7,46 Although less frequently reported, cases that were successfully treated with long-term DOAC have also been reported. 14,29,35,50 However, no studies have compared the two approaches. Progression or rethrombosis in patients on therapy with both VKA and DOAC has also been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,46 Although less frequently reported, cases that were successfully treated with long-term DOAC have also been reported. 14,29,35,50 However, no studies have compared the two approaches. Progression or rethrombosis in patients on therapy with both VKA and DOAC has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although IVC reconstruction is possible, it is only performed in cases where other treatment modalities failed. 16,50 Thrombolysis or thrombectomy can be performed to prevent chronic symptoms, such as residual pain, tenderness, and swelling. It has been shown that patients with IVC anomalies and thrombosis treated with thrombolysis are less likely to develop postthrombotic syndrome or thrombosis recurrence.…”
Section: Discussionmentioning
confidence: 99%